Strategi Humas TVRI Sumatera Utara dalam Pengelolaan Aplikasi Instagram Untuk Meningkatkan Citra Positif Pada Masyarakat di Sumatera Utara - Rahmanda, Rafli; Simamora, Irma Yusriana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Social media has become an important platform for broadcasting institutions such as TVRI North Sumatra to strengthen their positive image in the eyes of the public. In this context, managing the Instagram application has become a significant strategy in achieving this goal. This research aims to determine the Public Relations strategy of TVRI North Sumatra in utilizing the Instagram application to increase a positive image among the people of North Sumatra. By using a descriptive qualitative approach method. The results of this research reveal that they have adopted various strategies to increase their positive image through the Instagram application. The strategy includes a focus on quality content such as informative and engaging TV program trailers, interviews and coverage of events. This strategy involves creating content that is informative, interesting, and relevant to the interests of the people of North Sumatra, as well as active interaction with followers through comments, direct messages, and live broadcasts.